1990
DOI: 10.3109/03009749009097631
|View full text |Cite
|
Sign up to set email alerts
|

OM-8980 and D-Penicillamine in the Treatment of Rheumatoid Arthritis:A 12-Month Double-blind Randomized Study

Abstract: Forty patients with active rheumatoid arthritis were included in this monocentre double-blind study comparing the therapeutic efficacy and safety of the immunomodulator OM-8980 with that of D-penicillamine. After 12 months of treatment, the parameters of Ritchie index, duration of morning stiffness, pain assessed by a visual analogue scale and categories, number of swollen joints, grip strength and erythrocyte sedimentation rate (ESR) were all significantly improved with OM-8980, as was the case for the Ritchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In addition, Evans et at. Several controlled clinical studies on patients with RA have shown that an extract of E. coti given orally (OM-8980, Subreum | has a disease controlling effect [121][122][123][124][125]. Escherichia coli GroEL stress protein belongs to the hsp60 family, together with the structurally related mycobacterial hsp65 showing cross-reactivity with many bacteria [ 120].…”
Section: M0-8980mentioning
confidence: 99%
“…In addition, Evans et at. Several controlled clinical studies on patients with RA have shown that an extract of E. coti given orally (OM-8980, Subreum | has a disease controlling effect [121][122][123][124][125]. Escherichia coli GroEL stress protein belongs to the hsp60 family, together with the structurally related mycobacterial hsp65 showing cross-reactivity with many bacteria [ 120].…”
Section: M0-8980mentioning
confidence: 99%
“…The clinical efficacy of OM-8980 24 mg/day was shown to be comparable to that of penicillamine 500 mg/day (maintenance dosage) in a small (n = 34) single-centre study of 12 months' duration (table 11), [24] although further comparisons should also be made with a higher titrated penicillamine dosage (~ 750 mg/day). NSAID/corticosteroid use and global evaluation of efficacy were similar for both groups.…”
Section: Comparisons With Placebo or Other Slow-acting Antirheumatic mentioning
confidence: 94%
“…At final evaluation, reductions in Ritchie index, the number of swollen joints, duration of morning stiffness, pain and ESR, and increased grip strength were accompanied by a decrease in NSAID/corticosteroid use (table 11). [23,24] In 2 placebo-controlled trials, improvements were greater for patients treated with OM-8980, although intergroup differences did not always attain statistical significance (table II). [23,24] In 2 placebo-controlled trials, improvements were greater for patients treated with OM-8980, although intergroup differences did not always attain statistical significance (table II).…”
Section: Comparisons With Placebo or Other Slow-acting Antirheumatic mentioning
confidence: 98%
See 1 more Smart Citation
“…Oral lyophilised E. coli extract contains several bacterial heat shock proteins with immunomodulatory properties. The extract's clinical efficacy was equivalent to D -penicillamine in a placebo-controlled trial [50]. However, this extract is more likely to be a nonspecific immunomodulator than to induce antigen-specific tolerance.…”
Section: Translation Of Tolerising Immunotherapeutic Approaches In Ramentioning
confidence: 99%